Knowledge of patient safety level among undergraduate nursing students at Universiti Sains Malaysia - Jaimit, Adven Tsen Jaimieh (Universiti Sains Malaysia, 2024)
Patient safety (PS) is a critical aspect of healthcare, and healthcare professionals, especially nursing students, play a pivotal role in ensuring it. Hence, understanding the level of knowledge in patient safety is crucial to enhancing the quality of care and reducing adverse events in healthcare settings. This study aimed to determine the knowledge of patient safety level among undergraduate nursing students in Universiti Sains Malaysia (USM). A cross-sectional study of 96 undergraduate nursing students, randomly selected, was carried out at USM from February 1, 2024, to March 31, 2024. A validated 27-item survey questionnaire was used to measure participants’ knowledge of patient safety. The study population was described by descriptive statistics (means, standard deviations, frequencies and percentages). The Pearson correlation coefficient test was employed to determine the association between socio-demographic characteristics and patient safety knowledge score. The mean age of participants was 23.00 ± 2.00 years old. Of the participants, 64.6% had a good knowledge level of patient safety, whereas the remainder, 35.4%, had moderate knowledge of patient safety. A significant correlation was observed between participants’ patient safety knowledge and gender (p=0.006). There was no statistically significant association between the knowledge score and age (p=0.885), practical duration (p=0.421), and level of study (p=0.421), respectively. Overall, students reported that they were more confident in their knowledge about patient safety gained in the clinical setting than in the classroom setting. Therefore, enhancing undergraduate nursing students' knowledge of patient safety requires a comprehensive approach that integrates classroom and clinical settings.